Contextualization of the Concept of 'Antaradlin' as a Legal Guarantee of On-Line Buying and Selling Transactions - Eva Andriani; Arifatul Ma'ani; Syovinatus Sholicha (Journal of Social Research, 2023)
'Between the meaning of voluntary being an important part of the practice of buying and selling, practically there must be a marker that proves that both parties are equally willing in a transaction the marker is called a contract in the form of a certain shigat. Thus, the interadlin principle, is really rated abash. Over time that is always developing, buying and selling online becomes a solution that greatly facilitates the practice of buying and selling, on the other hand online media is also the culprit of fraud. Therefore, in the current context, the principle between adlin and its provisions must be contextualized with the current era. So with a rule that reads "the origin of muamalah is mubah" then the transformation of the principle of voluntary can be developed in accordance with the present. Voluntary conclusions in the principle of buying and selling transactions in online buying and selling practices are; 1) the seller must openly and honestly state the real goods to be traded, 2) the buyer must be in detail the real goods that have been described before buying, 3) both parties are equally ready to use bang Together to bind the truth of the transaction